2010
DOI: 10.1016/j.jcmg.2010.09.016
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Age With Regional Aortic Stiffness and Diameter

Abstract: The greatest difference in aortic stiffness occurs in the abdominal region, whereas the greatest difference in diameter occurs in the ascending aorta, which may help offset an increase in wall stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
182
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(204 citation statements)
references
References 27 publications
22
182
0
Order By: Relevance
“…9,10 The observation of markedly higher stiffness in the ascending as compared to the descending aorta, which is only a dozen centimeters downstream, 17 is not supported by studies of regional transit time PWV, which found a persistent positive stiffness gradient moving distally along the aorta in older people. 18 After adjusting for longitudinal strain, circumferential strain in the ascending aorta was comparable to strain in the descending aorta, which suggests that with age, proximal Figure 7. Lumen area strain of the ascending and descending aorta for women (red) and men (blue).…”
Section: Discussionmentioning
confidence: 94%
“…9,10 The observation of markedly higher stiffness in the ascending as compared to the descending aorta, which is only a dozen centimeters downstream, 17 is not supported by studies of regional transit time PWV, which found a persistent positive stiffness gradient moving distally along the aorta in older people. 18 After adjusting for longitudinal strain, circumferential strain in the ascending aorta was comparable to strain in the descending aorta, which suggests that with age, proximal Figure 7. Lumen area strain of the ascending and descending aorta for women (red) and men (blue).…”
Section: Discussionmentioning
confidence: 94%
“…Area-based parameters and aortic volume allow to quantitatively describe aortic enlargement, that has been correlated with arterial stiffening [45] and, ultimately, to systemic risk factors such as hypertension. Among possible scenarios, an increased aortic volume, as the one observed here for PG ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The thoracic aorta increases in diameter, elongates, and stiffens with advancing age 1, 2, 3, 4. Aortic arch width (AAW)5, 6 also increases with older age.…”
Section: Introductionmentioning
confidence: 99%
“…Aortic arch width (AAW)5, 6 also increases with older age. These changes in aortic geometry are cross sectionally associated with excess burden of undesirable hemodynamic and cardiac structural changes 1, 4, 6. Furthermore, increasing aortic stiffness may be more a precursor than a result of hypertension 7.…”
Section: Introductionmentioning
confidence: 99%